JURIDICAL ANALYSIS OF CRIMINAL LIABILITY OF PERPETRATORS OF COLLECTIVE VIOLENCE IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 1245/PID.B/2025/PN MDN - Rudi Simamora; Muhammad Ridwan Lubis (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the results of the study, it shows that the elements of the crime of violence committed together consist of the element of whoever, the element of openly, the element of joint force, the element of using violence, the element against people or goods. The proof of the crime of violence committed together in Decision Number 1245 / Pid.B / 2025 / PN Mdn is appropriate, namely the proof of the element of whoever and the element of intentionally in public together committing violence against people or goods resulting in the destruction of goods or causing serious injury has been proven based on evidence of witness statements, statements of the defendant, written evidence, and evidence of indications. The responsibility of the perpetrator of the crime of violence committed together in Decision Number 1245 is to be sentenced to 3 years in prison. The decision of the panel of judges is inappropriate and too light